2017
DOI: 10.13057/biodiv/d180406
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: New record of wild banana (Musa balbisiana Colla) in West Kalimantan, Indonesia

Abstract: Sunandar A. 2017. Short Communication: New record of wild banana (Musa balbisiana Colla) in West Kalimantan, Indonesia. Biodiversitas 18: 1324-1330. Kalimantan Island (Indonesia) is part of the center of origin and diversity of wild bananas in Indo-Malesia region. West Kalimantan is one of province in Kalimantan Island. However, only a little information is available about diversity of wild bananas in West Kalimantan. The aims of this study were to study a possible new record of wild banana species in Nipah Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This study revealed that the IBF could prevent the increased FGF21 expression in malnutrition model. This might be due to the protein (8.2%) contained in the banana flour (Sani, 2015; Chalvon-Demersay et al , 2016). Klutuk banana flour consists of essential amino acids histidine, threonine, lysine and leucine (Sani, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study revealed that the IBF could prevent the increased FGF21 expression in malnutrition model. This might be due to the protein (8.2%) contained in the banana flour (Sani, 2015; Chalvon-Demersay et al , 2016). Klutuk banana flour consists of essential amino acids histidine, threonine, lysine and leucine (Sani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the protein (8.2%) contained in the banana flour (Sani, 2015; Chalvon-Demersay et al , 2016). Klutuk banana flour consists of essential amino acids histidine, threonine, lysine and leucine (Sani, 2015). The protein composition in klutuk banana flour might lead to the inactivated general control nonderepressible 2 and inhibited eukaryotic translation initiation factor 2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations